Equipment for pulsed thermal treatment of the surfaces of materials by a low-energy electron beam - Devyatkov V. N.; Koval N. N. Nikolay Nikolaevich; Grigoriev S. V.; Teresov A. D. (2013, 2013)
This paper describes the design of the equipment used for studying the treatment of the surfaces of metal specimens and presents the results of studies of a source that produces a low-energy high-current electron beam. An electron beam with a current of up to 300 A and pulse duration of 20−200 µs is generated in a gas-filled diode with a plasma cathode at a pulse repetition rate of 0.3−15 s−1 and at an accelerating voltage of up to 25 kV. The space-charge-compensated electron beam is transported in a longitudinal magnetic field for a distance of 20−30 cm to the region of its interaction with a solid. At a current density of up to 20 A/cm2, the beam power density proves to be sufficient for melting a metal surface by means of one or several pulses.